Evolution of X-ray irradiation during the 1999–2000 outburst of the black hole binary XTE J1859 + 226. Issue 1 (8th October 2018) - Kimura, Mariko; Done, Chris
Abstract: X-ray irradiation in X-ray binaries is thought to control the behaviour at the outer disc, which is observable mainly at optical wavelengths. It is generally parametrized phenomenologically, but it can also be predicted from theoretical models of irradiated discs and their coronae/winds. We test these models using five multiwavelength Hubble Space Telescope and quasi simultaneous Rossi X-Ray Timing Explorer (RXTE) data sets from the black hole binary XTE J1859 + 226. These show how the reprocessed optical emission changes during outburst as the source fades from the very high/intermediate state at ∼0.4 L Edd down through the high/soft state towards the transition to the hard state at ∼0.02 L Edd . The models are able to reproduce the small change in reprocessing efficiency as the source flux decreases by a factor of two, and the spectrum softens from the very high/intermediate state to the bright high/soft state. However, the low luminosity high/soft state as well as the transition spectrum show more complex behaviour that is not well described by current models. We suggest the disc geometry has changed drastically during the outburst, probably due to tidal forces, and that the disc is no longer in steady state at the late stage of the outburst.